The Impact of International Transportation Interconnection on the Quality of Urban Economic Growth - Sui, Hongguang; Wang, Zixuan; Liu, Jiabei; Zhao, Weixing (Frontiers in Environmental Science, 2022)
The China-Europe Freight Train is a link connecting Eurasia and a vital carrier to promote regional economic cooperation. This paper uses principal component analysis to measure the quality of China's city-level economic growth. Based on the data from 273 prefecture-level cities in China from 2003 to 2016, the multi-period DID model is used to test the impact of the opening of the China-Europe Freight Train on the quality of urban economic growth. Firstly, the basic results show that the opening of the China-Europe Freight Train significantly improves the quality of economic development of node cities, which remains robust under a series of robustness tests. Secondly, the heterogeneity test shows that China-Europe Freight Train is more conducive to improving the quality of economic growth in inland cities and cities with small freight volumes in central and western China. There is no significant difference in the impact of road infrastructure construction in different level cities. Thirdly, the mechanism test shows that the opening of the China-Europe Freight Train has a significant impact on improving the quality of economic growth, with no positive effect on stability and sustainability. The construction of the China-Europe Freight Train is still under development. It is necessary to take complete account of the situation of different cities in scientific planning, improve its driving effect on stability and sustain while maintaining efficiency, then optimize the economic benefits of the freight train.